2023
DOI: 10.1021/acsaem.2c03283
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Encapsulated Multimetallic Hybrid Electrocatalyst for Overall Water Splitting and Urea Oxidation

Abstract: Overall water splitting is a hot topic in the development of green energy, but it cannot be generalized on a large scale due to the lack of low-cost and highly efficient overall water-splitting catalysts. As a result, currently, the exploitation of stable and nonprecious metal catalysts with elevated performance has become a research focus in overall water splitting. Here, we introduce a multicomponent material (Ni/MoC/Ti3C2T x @C) by a strategy of the combination of electrostatic assembly and elevated-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…The peak of Nb–P does not appear in Figure b, indicating that the P element was not introduced in the form of Nb–P bond and may exist in the form of Nb–C–P, C–P, and O–PO . From Figure b, the C 1s spectrum of P–Nb 4 C 3 T x and Nb 4 C 3 T x presents five primary peaks, which are put down to 288.6 eV (O–CO), 286.3 eV (C–H), 285.7 eV (C–P), 284.8 eV (C–C), and 282.2 eV (C–Nb). , The XPS spectrum of P 2p for P–Nb 4 C 3 T x and Nb 4 C 3 T x presents the main peaks at about 134.3 and 133.5 eV, and they are relevant to O–PO 2p 1/2 and 2p 3/2 , showing the successful introduction of the P element (Figure c). The formation of O–PO bonds can also prove that the P atom combines with the Nb 4 C 3 T x surface functional group (−O) to form an efficient electrocatalyst.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The peak of Nb–P does not appear in Figure b, indicating that the P element was not introduced in the form of Nb–P bond and may exist in the form of Nb–C–P, C–P, and O–PO . From Figure b, the C 1s spectrum of P–Nb 4 C 3 T x and Nb 4 C 3 T x presents five primary peaks, which are put down to 288.6 eV (O–CO), 286.3 eV (C–H), 285.7 eV (C–P), 284.8 eV (C–C), and 282.2 eV (C–Nb). , The XPS spectrum of P 2p for P–Nb 4 C 3 T x and Nb 4 C 3 T x presents the main peaks at about 134.3 and 133.5 eV, and they are relevant to O–PO 2p 1/2 and 2p 3/2 , showing the successful introduction of the P element (Figure c). The formation of O–PO bonds can also prove that the P atom combines with the Nb 4 C 3 T x surface functional group (−O) to form an efficient electrocatalyst.…”
Section: Resultsmentioning
confidence: 95%
“…The C dl value of Nb 4 C 3 T x increased significantly after lowtemperature phosphating treatment, which indicated that the active site of the reaction might be exposed more, thus enhancing the electrocatalytic performance of Nb 4 C 3 T x . 27 Therefore, the electrical conductivity was measured to understand the HER performance of P−Nb 4 C 3 T x . The high conductivity is contributed to improve the HER performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks of Mo 3d in Ni 2 P-MoC/C-CFs and MoC/C-CFs could be deconvoluted into three doublets, corresponding to the three valence states (+2, +4, and +6) of Mo on the surface. The Mo 2+ peaks at 228.6 and 231.6 eV, respectively, are attributed to the Mo-C bond and are generally considered to be the electrocatalytic active centers [ 28 ]. Herein, the existence of the Mo 4+ and Mo 6+ species can be attributed to the surface oxides formed during the pre-oxidation process [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, transition metal-based compounds such as carbides [ 8 , 9 , 10 , 11 ], phosphides [ 12 , 13 , 14 ], sulfides [ 15 , 16 , 17 ], oxides [ 18 , 19 , 20 ], borides [ 21 , 22 , 23 ], and nitrides [ 24 , 25 , 26 ] have been reported to be used in the HER electrocatalysts and shown good catalytic performance. Among them, molybdenum carbide (Mo x C) has attracted extensive attention because of its different Mo valence, adjustable phase composition, high abundance, high chemical stability, and d-band electronic structure, which is similar to Pt-based catalysts [ 27 , 28 , 29 , 30 ]. However, single MoC particles are prone to agglomerate at high temperatures, and the hydrogen adsorption capacity of pure MoC is so strong that the conductivity is poor [ 31 ], which affects its performance for the HER.…”
Section: Introductionmentioning
confidence: 99%